Saving Emma - Eskens, Allen, 1963- (Mulholland Books/Little, Brown and Company, 2023)
"When Boady Sanden first receives the case of Elijah Matthews, he's certain there's not much he can do. Elijah, who believes himself to be a prophet, has been locked up in a psychiatric hospital for the past four years, convicted of brutally murdering the pastor of a megachurch. But as a law professor working for the Innocence Project, Boady agrees to look into Elijah's file. When he does, he is alarmed to find threads that lead back to the death of his colleague and friend, Ben Pruitt, a man shot to death four years earlier in Boady's own home. Ben's daughter, Emma, has lived with Boady and Boady's wife Dee ever since that awful night. Now fourteen years old, Emma has been growing distant, and soon makes a fateful choice that takes her far from the safety of her godparents. Desperate to bring her home, and to free an innocent man, Boady must do all he can to investigate Elijah's case while fighting to save the family he has deeply come to love"--Dust jacket flap.